2015
DOI: 10.1016/j.ijrobp.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Change of Maximum Standardized Uptake Value Slope in Dynamic Triphasic [18F]-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Distinguishes Malignancy From Postradiation Inflammation in Head-and-Neck Squamous Cell Carcinoma: A Prospective Trial

Abstract: Purpose/Objectives(s) The positive predictive value (PPV) of post-radiation (RT) 3-month FDG-PET/CT imaging in head and neck squamous cell carcinoma (HNSCC) is limited. Dynamic data acquisition and analysis was evaluated for PPV improvement, utilizing a triphasic PET/CT technique. Methods and Materials We prospectively enrolled HNSCC patients who completed RT, with scheduled 3-month post-RT FDG-PET/CT. Patients underwent our standard whole-body PET/CT scan at 90 minutes, with the addition of head and neck PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…Keski-Säntti et al [62] reported that PET/CT conducted about 3 months after therapy has sensitivity, specificity, positive predictive value (PPV), and NPV of 59%, 94%, 71%, and 91% for detecting residual disease in the primary sites, and 95%, 100%, 100%, and 93% in the nodes, respectively. Recently, Anderson et al [63] used SUV measurements at 60, 90, and 120 minutes and found that change of maximum SUV slope after 90 minutes more accurately identified non-recurrence in positive or equivocal sites than using SUV at one point. This finding suggests that quantitative measures from pharmacokinetic analysis of PET data may provide more reliable and accurate imaging markers to identify residual tumor after therapy.…”
Section: Treatment Response Monitoring and Predictionmentioning
confidence: 99%
“…Keski-Säntti et al [62] reported that PET/CT conducted about 3 months after therapy has sensitivity, specificity, positive predictive value (PPV), and NPV of 59%, 94%, 71%, and 91% for detecting residual disease in the primary sites, and 95%, 100%, 100%, and 93% in the nodes, respectively. Recently, Anderson et al [63] used SUV measurements at 60, 90, and 120 minutes and found that change of maximum SUV slope after 90 minutes more accurately identified non-recurrence in positive or equivocal sites than using SUV at one point. This finding suggests that quantitative measures from pharmacokinetic analysis of PET data may provide more reliable and accurate imaging markers to identify residual tumor after therapy.…”
Section: Treatment Response Monitoring and Predictionmentioning
confidence: 99%
“…However, in our study, patients have been scanned with a standard clinical PET imaging protocol, which is broadly used in other institutes [25][26][27], which increases the applicability of our findings. In addition, many recent studies have shown the prognostic value of SUV quantification in patients with head and neck cancer [8,9]. For example, Semrau et al have reported that an absolute post-treatment SUV-max <10 has the best discriminatory power for long-term tumor-free survival and overall survival in patients with head and neck squamous cell carcinoma after the induction chemotherapy [28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Combined PET/CT scan has improved the staging, treatment evaluation, and detection of recurrent disease in patients with head/neck cancer [7][8][9]. The sensitivity and specificity of PET for the detection of malignant cervical lymph nodes have been reported in 61-96%, and 80-99% range, respectively; compared with CT/MRI sensitivity of 53-82%, and specificity of 71-97% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This can also allow for less patient morbidity. However, it should be noted that 18 F-FDG PET/CT has a low PPV because there are high rates of false positives that often lead to additional imaging and unnecessary biopsies 28,29 and neck dissections in individual cases.…”
Section: Radiation Treatment Response Assessmentmentioning
confidence: 99%